GANDHI’S IDEOLOGY-RAJA RAO-MOORTHY IN KANTHAPURA - Prabhakar, R. (International Journal of Research -GRANTHAALAYAH, 2016)
Kanthapura is considered the magnum opus of Raja Rao which portrays the considerable influence of Gandhi’s ideology on the sleepy and remote village. Raja Rao is very successful in carving out the real picture of Indian village in pre-independence era. Kanthapura is the microcosm of the Indian traditional society and what happened in Kanthapura was also happened in India during 1919-1930. It is not only a political novel, but also a novel which concerns with socio-religious and economic transformation during the struggle for independence. Though his novels stray far afield, his heart is clanged to his sublime ancient Hindu tradition. The novel can be considered Gandhi-epic. It depicts impact of Gandhi’s Ideology on the paralytic Indian masses. Gandhi’s influential personality and his ideology is felt everywhere in the novel. Indeed, Gandhi doesn’t appear in this novel personally, but the plot of the novels revolves around his ideology. This research article, ‘Gandhi’s Ideology-Raja Rao-Moorthy in Kanthapura,’ aims at how the Gandhi’s ideology influenced Raja Rao which resulted in the creation of the character of Moorthy. It also focuses on how Moorthy, under the influence Gandhi, tries to inspire the people towards the Freedom Struggle. Gandhi is the way, the truth, life to Raja Rao. Similarly, Gandhi’s ideology is the way, the truth, and the life to Moorthy in the novel Kanthapura.